Designing an Industry-Oriented Problem-Based Learning Model to Enhance Vocational High School Students' Work Readiness - Bambang Sudarsono; Pratama, Wegig (Jurnal teknologi pendidikan (Jakarta, Indonesia), 2025)
Industry-Oriented Problem-Based Learning Model (I-ProBL) was developed to address the work readiness of vocational high school graduates that are not fully aligned with industry needs. This study aims to develop and test the effectiveness of the I-ProBL model in improving the skills of vocational high school students. The model used is Research and Development (R&D) with the ADDIE model consisting of five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were 270 students, 6 teachers, 3 industry practitioners, and 2 vocational education experts in three vocational high schools in Yogyakarta. The object of this study is the I-ProBL learning model applied in the vocational high school curriculum. Data collection techniques were carried out through interviews, validation questionnaires, and tests. The instruments used included interview grids, model feasibility validation questionnaires, and student practice test instruments. Data analysis was carried out descriptively quantitatively by calculating the average value and percentage of student skill improvement before and after the implementation of the I-ProBL model. The results showed that the I-ProBL model has a high level of suitability with industry needs (4.6, very good category) and relevance to the world of work (4.7, very good category). the implementation of this model increased the average student grades by 20.1% to 21.2% and increased student engagement in learning (85%) and their readiness to face the world of work (90%). The impact of this study shows that I-ProBL can be an effective solution in improving the quality of vocational school graduates and strengthening the relationship between schools and industry. However, for more optimal implementation, it is necessary to improve teacher training, provide more adequate facilities, and support policies that encourage closer collaboration between vocational schools and the industrial world.